THE YIELD OF A 11 YEARS OLD SASKATOON BERRY (AMELANCHIER ALNIFOLIA NUTT.) CULTURE FROM ARAD COUNTY, WESTERN ROMANIA - Ruben BUDĂU; Cristian Mihai ENESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Recently, in Romania special attention was given to the culture of Saskatoon berry (Amelanchier alnifolia Nutt.), a species originating from North America, whose berries are very appreciated both for their nutritional and medicinal values. The aim of this study was to highlight the yield of a culture installed in Bărzani Farm, Arad county, Romania.. The plants were produced in 2012 from seeds originating from Alberta (Canada). In the first two growing seasons the plants were kept into a nursery and specific treatments were applied. In Autumn 2013, the plants were transferred to two experimental plots, with a total area of 0.74 hectares, and a 3 m x 1 m planting scheme was adopted (i.e. 3 meters between the rows and 1 meter between the plants in the same row). Starting with 2018 different fertilizers were applied and soil analysis were performed. In most of the cases as regards the main micro- and macro-elements from the soil increasing trends were recorded thanks to the applied fertilizers. As regards the harvested quantities in the last five growing seasons, they grew from 1,250 kg (in 2018) to 6,800 kg (in 2022), meaning that, on average, each plant produced from 0.5 kg (in 2018) up to 2.7 kg (in 2022). The results recorded in the two experimental plots from Bărzani Farmrepresent an important step in the breeding program of his species in Romania.